Assessing the impact of public health interventions on the transmission of pandemic H1N1 influenza a virus aboard a Peruvian navy ship. Issue 3 (10th February 2014) - Vera, Delphis M.; Hora, Ricardo A.; Murillo, Anarina; Wong, Juan F.; Torre, Armando J.; Wang, David; Boulay, Darbi; Hancock, Kathy; Katz, Jacqueline M.; Ramos, Mariana; Loayza, Luis; Quispe, Jose; et al.
<x xml:space="preserve">Abstract</x> Background Limited data exist on transmission dynamics and effectiveness of control measures for influenza in confined settings. Objectives To investigate the transmission dynamics of a 2009 pandemic H1N1 influenza A outbreak aboard a Peruvian Navy ship and quantify the effectiveness of the implemented control measures. Methods We used surveillance data and a simple stochastic epidemic model to characterize and evaluate the effectiveness of control interventions implemented during an outbreak of 2009 pandemic H1N1 influenza A aboard a Peruvian Navy ship. Results The serological attack rate for the outbreak was 49·1%, with younger cadets and low‐ranking officers at greater risk of infection than older, higher‐ranking officers. Our transmission model yielded a good fit to the daily time series of new influenza cases by date of symptom onset. We estimated a reduction of 54·4% in the reproduction number during the period of intense control interventions. Conclusion Our results indicate that the patient isolation strategy and other control measures put in place during the outbreak reduced the infectiousness of isolated individuals by 86·7%. Our findings support that early implementation of control interventions can limit the spread of influenza epidemics in confined settings.